Efficacy and safety profile of COVID-19 vaccine in cancer patients: a prospective, multicenter cohort study - Yasin, Ayse Irem; Aydin, Sabin Goktas; Sumbul, Bilge; Koral, Lokman; Simsek, Melih; Geredeli, Caglayan; Gumus, Mahmut (Taylor & Francis Ltd, 2022)
Aim: To compare the seropositivity rate of cancer patients with non-cancer controls after inactive SARS-CoV-2 vaccination (CoronaVac) and evaluate the factors affecting seropositivity. Method: Spike IgG antibodies against SARS-CoV-2 were measured in blood samples of 776 cancer patients and 715 non-cancer volunteers. An IgG level >= 50 AU/ml is accepted as seropositive. Results: The seropositivity rate was 85.2% in the patient group and 97.5% in the control group. The seropositivity rate and antibody levels were significantly lower in the patient group (p < 0.001). Age and chemotherapy were associated with lower seropositivity in cancer patients (p < 0.001). Conclusion: This study highlighted the efficacy and safety of the inactivated vaccine in cancer patients. Clinical Trials Registration: ClinicalTrials.gov) Plain language summary Cancer patients are at high risk for infection with SARS-CoV-2 and of developing the associated disease, COVID-19, which therefore puts them in the priority group for vaccination. This study evaluated the efficacy and safety of CoronaVac, an inactivated virus vaccine, in cancer patients. The immune response rate, defined as seropositivity, was 85.2% in the cancer patient group and 97.5% in the control group. The levels of antibodies, which are blood markers of immune response to the vaccine, were also significantly lower in the patient group, especially in those older than 60 years and receiving chemotherapy. These results highlight the importance of determining the effective vaccine type and dose in cancer patients to protect them from COVID-19 without disrupting their cancer treatment.
Keywords: cancer; chemotherapy; CoronaVac; COVID-19; COVID-19 vaccines; immunotherapy; malignancy; SARS-CoV-2